2003
DOI: 10.1097/00126334-200310010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Access to Antiretroviral Treatment, Incidence of Sustained Therapy Interruptions, and Risk of Clinical Events According to Sex

Abstract: Objectives of the study were to assess the differences between sexes in the likelihood of starting antiretroviral therapy (ART), in rates of sustained discontinuation from highly active antiretroviral therapy (HAART), and in clinical progression. In a multicenter cohort study (I.Co.N.A. Study), 2323 men and 1335 women previously naive to antiretrovirals were enrolled. As of September 2002, 807 women and 1480 men started ART. The median time to starting ART was 28 weeks for women and 17 weeks for men (P = 0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
5
26
1
Order By: Relevance
“…The authors concluded that there was no significant evidence of a sex difference in virologic, immunologic, or clinical outcomes after starting HAART. These findings are in agreement with results of other studies examining differences in response to HAART in HIV-infected men and women [12,19,20].…”
Section: Are There Sex Differences In Response To Antiretroviral Thersupporting
confidence: 93%
“…The authors concluded that there was no significant evidence of a sex difference in virologic, immunologic, or clinical outcomes after starting HAART. These findings are in agreement with results of other studies examining differences in response to HAART in HIV-infected men and women [12,19,20].…”
Section: Are There Sex Differences In Response To Antiretroviral Thersupporting
confidence: 93%
“…3 With the alarming increase in the HIV/AIDS pandemic in developing countries, and the limited accessibility and availability of highly active antiretroviral therapy (HAART), the majority of people living with HIV/AIDS (PLHA) continue to suffer with the disease, with a serious impact on their well-being. 4,5 A considerable amount of research have been conducted in many countries on the variables related to the psychological well-being of different populations of PLHA. [6][7][8][9][10] Current research confirms that receiving social support from significant social network members can promote positive psychological adjustment in people living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] However, studies examining sex differences in retention or interruption of therapy have been limited in the generalizability of their findings due to being performed in the context of clinical trials, in resourcelimited settings, or at single clinical sites. [17][18][19][20] Where racial and HIV risk disparities in retention and HIV outcomes are concerned, many of the aforementioned studies have also noted significant differences for persons of black race and those with injection drug use (IDU), 4,5,9,12,14,16 although at least one clinical cohort has noted a resolution of racial disparities in HIV outcomes in its recent history. 21 These studies have also been limited by lack of information on ART use or have used different methods to adjust for the ART status of their participants while examining retention outcomes.…”
mentioning
confidence: 99%